LANGUAGE FEATURES AND CAUSES OF SUICIDE CASE FROM FORENSIC LINGUISTICS POINT OF VIEW - Apriyanto, Sigit (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
This study aims to describe the psychological process, language features and the cause?s factors of student's suicide notes. This study explores the power of linguistic variables to uncover the hidden meaning of suicide notes. This analysis uses computerized text analysis namely Linguistic Inquiry and Word Count (LIWC) program and forensic semantic analysis. The primary data source of this study is the student's suicide notes in the form of written texts. The stages of data analysis are analyzing the data, coding, trying to find themes derived from data and writing 'models' that are found based on the coding that has been completed. The focus of semantic analysis in a forensic context is the understanding and interpretation of the hidden meaning of language. The contents of the linguistic forensic text of suicidal students' intentions are the use of unusual vocabulary in context, using and showing sad, angry, and negative emotion vocabulary, a direct speech addressed to a person or his/her relations, mentioning something that is needed, desired, there is no doubt, the text between 50 to 300 words, the situational context is not indicated. The factors that cause students to commit suicide are family, social environmental and economic factors.